Problem Based Learning Assisted by Plickers Application in Improving Critical Thinking Ability - Irawati, Tri Novita; Mahmudah, Muhlisatul (Journal of Education and Learning Mathematics Research (JELMaR), 2024)
Students' critical thinking ability is one of the problems that needs serious attention, especially in the field of mathematics learning. Through Problem Based Learning assisted by the Plickers application, it is hoped that this can be a solution to overcome this problem. This research is classroom action research which consists of 2 cycles which include planning, action, observation, reflection. The data collection process takes the form of tests, observations and documentation. The subjects of this research were students in class VII C MTs. Ma'arif Ambulu numbered 26 students. The results of the research showed that students' critical thinking abilities were significant, namely in cycle I the average percentage was 57.04% (poor) and in cycle II 84.79% (good).